AN ANALYSIS OF EXPRESSIVE SPEECH ACTS USED IN CRAZY RICH ASIAN MOVIE - Rahmawati, Risa Dewi (Journal of Language and Literature, 2021)
This research studies about expressive speech act in Crazy Rich Asian movie, the objectives of the research are to describe (1) to analyze the type of expressive speech act found in Crazy Rich Asian movie and (2) to describe the S-P-E-A-K-I-N-G model used in Crazy Rich Asian movie. This research used theory from Searle (1985) and Hymes (1974) in analyzing the data. There are twelve expressive speech act mentioned by Searle; apologize, thank, condole, congratulate, complain, lament, protest, deplore, boast, compliment, greet, and welcome. This research used descriptive qualitative method. The researcher collected expressive speech act utterances as the data to be analyzed; in analyzing the data the researcher used S-P-E-A-K-I-N-G model. The results showed that there were 52 data of expressive speech act and only ten types of expressive speech found in Crazy Rich Asian movie, some of the expressive types appeared except expressive act of condole and boast. the researcher used SPEAKING model is to know how the meaning of the social context, the purpose of the interaction in detail and describe them into analysis text. From the data analysis it shows that the types of expressive speech act that oftenly come up are apologize, thank and compliment. It shows that the characters in the Crazy Rich Asian movie more showed politeness and friendly attitude to others.